Предмет: Математика, автор: alekseifedorov501

СРОЧНО ПОМОГИТЕ !!! 4. Упрости выражение: ) a) -3x+1,6 - 2x -24 Б) — 4-у-(-6)х; e) -0,5. (x-6) + - ) ​

Приложения:

Ответы

Автор ответа: Аноним
3

\displaystyle 1)-3\frac{1}{2}x+1,6-2x-2\frac{1}{5}=-\frac{7}{2}x+\frac{8}{5}-2x-\frac{11}{5}=-\frac{11}{2}x-\frac{3}{5}=-5,5x-0,6\\\\ 2)-4\frac{1}{3}y*(-6)x=-\frac{13}{3}y*(-6)x=13y*2x=26xy\\\\ 3)-0,5(\frac{2}{3}x-6)+\frac{1}{3}=-\frac{1}{2}(\frac{2}{3}x-6)+\frac{1}{3}=-\frac{1}{3}x+3+\frac{1}{3}=-\frac{1}{3}x+\frac{10}{3}


alekseifedorov501: спасибо
Похожие вопросы
Предмет: Қазақ тiлi, автор: Алина11111115111111